2019
DOI: 10.33549/physiolres.934127
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Left Ventricle Myocardium in an SHR Congenic Line With Ameliorated Cardiac Fibrosis

Abstract: Metabolic syndrome and one of its manifestations, essential hypertension, is an important cause of worldwide morbidity and mortality. Morbidity and mortality associated with hypertension are caused by organ complications. Previously we revealed a decrease of blood pressure and an amelioration of cardiac fibrosis in a congenic line of spontaneously hypertensive rats (SHR), in which a short segment of chromosome 8 (encompassing only 7 genes) was exchanged for a segment of normotensive polydactylous (PD) origin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Martinez-Gonzalez et al demonstrated that NOR-1 is transiently expressed in coronary SMCs in response to balloon dilatation [31], which may be of great importance in CABG. NR4A1 and NR4A3 have been described as receptors regulating cell differentiation, proliferation, inflammation and apoptosis, as well as being particularly important for their impact on the development of cardiovascular diseases [32]. It is known that Neuron-derived orphan receptor 1 (NOR1) regulates the proliferation of blood vessel smooth muscle cells (VSMC).…”
Section: Discussionmentioning
confidence: 99%
“…Martinez-Gonzalez et al demonstrated that NOR-1 is transiently expressed in coronary SMCs in response to balloon dilatation [31], which may be of great importance in CABG. NR4A1 and NR4A3 have been described as receptors regulating cell differentiation, proliferation, inflammation and apoptosis, as well as being particularly important for their impact on the development of cardiovascular diseases [32]. It is known that Neuron-derived orphan receptor 1 (NOR1) regulates the proliferation of blood vessel smooth muscle cells (VSMC).…”
Section: Discussionmentioning
confidence: 99%